Penguatan Keperibadian Anggota Angkatan Tentara Malaysia Melalui Program Pendidikan Islam Fiqih Ibadah - Burhanuddin Jalal (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2019)
Absctract: The stability and strength of a military organization is generally based on three main aspects: the strength of firepower, the ability of mobility, and the strength of the fighting spirit among its personnel. To enhance the strength of fighting spirit among members of the Malaysian Armed Forces, the Malaysian Armed Forces Religious Corps (Kor Agama Angkatan Tentara – KAGAT) has been tasked to achieve this via Islamic Education approach. One of the modules implemented by KAGAT for this purpose is using Fardu Ain Education Module (Modul Pendidikan Islam Fardu Ain – PIFA). This paper discusses the development and implementation of the PIFA module from the history of execution until it becomes a compulsory requirement for the promotion process and career path especially among members of different ranks in the Malaysian Armed Forces. This paper employs the qualitative design methods where historical review and analysis of available documents are carried out. The findings indicate that Islamic education in the Malaysian Armed Forces that started since the establishment of KAGAT in 1985, has undergone several improvement processes until the PIFA module was received as a module that must be attended by members of different ranks. It was found that this module has had important implications in strengthening and appreciation of Islam among the personnel of the Malaysian Armed Forces. Keyword: Internalization, Islamic dacwah, army spiritual